Žanry oficialʹno-delovogo stilâ v zerkale russkoj slengovoj metafory - Balašova, Lûbovʹ V. (Stylistyka, 2008)
The metaphor - one of basic means of forming of the vocabulary of contemporary Russian slang - is been regularly used when the nomination of various speech genres of the official style takes place. Thus, the language picture of the world is forming, where the negative attitude towards official speech communication has been reflected. In a way, it demonstrates distrust of common people to the authority and power institutes.